(3MGUd GdeSGFds - (3CHh ESMGb EHQGgje Hf eMeO GdeYQha HZVaQ GdJHQjRis; (3Mfjf Hf GSMGb , CHh RjO Mfjf Hf GSMGb GdYHGOj,J (B260 (3g` s ((3NSQh aJM Gddg GdYWGQ GdeJWHH s)
(3ChdgG (B:s
(3bGd ehdGfG deG aQZJ ef GNJUGQ GdehShe HeSGFd Mfjf hJLQjOg Yf GdRhGFO GdWH LRGAGJ fXQi hYedi s
(3BNQgG (B:s
(3CeG JHSW GdMQGQI hEeG HbHVgG hOaYI Ch eJOQLkG Ch eJQOOkG Ch LYd GdOeGY HGQGOkG QWHkG hGddg CYde hCMce s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs